Methodological Framework for Centrifugal Pump Performance Analysis Using CFD Simulation - Ahmed Gaddour; Ramadan Khalifa Ramadan; Khalid Mahmudi (African Journal of Advanced Pure and Applied Sciences, 2025)
To drain water from the lower reservoir to the upper reservoir, a pump is needed to move it. The pump will work optimally if the pump has an installation that matches the pump’s ability to work. The guidelines for making pump installations are capacity (Q) and pressure height ( H) required to pump the water. This water is first collected in the lower reservoir and then sent to the upper reservoir. A pump is a machine that converts mechanical energy into pressure energy. According to some literature, there are several types of pumps, but what is commonly used is the type of centrifugal pump. This pump designed will be modeled and simulated using CFD FLUENT v 6.1.22 which will then be compared with the performance generated manually. In this case, FLUENT CFD makes it very easy to adjust according to real conditions. Then the conclusion is based on the results of the pump characteristics that have been made with the same impeller shape and pump rotation, it can be concluded that the large capacity (Q) is inversely proportional to the amount of pressure height (H). The greater the capacity, the smaller the pressure, or vice versa, the smaller the capacity, the greater the pressure and the head capability that the pump can serve based on the simulation is greater than the calculation results.